Examining the Service Quality of Prison Education for Women in Cambodia: A Case Study of the 2nd Correctional Center - Reth Vicheka; Seng Dararaksmey (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose: This study evaluates the service quality of prison education for women at Cambodia’s 2nd Correctional Center by comparing prisoners’ expectations with their actual experiences. It identifies institutional and psychosocial barriers affecting service delivery, learning outcomes, and program effectiveness. Methodology: A mixed-methods approach was used. Quantitative data were collected through structured surveys of 170 women prisoners and analyzed using a paired t-test. Qualitative insights were drawn from semi-structured interviews with 20 prisoners and 5 prison officers, analyzed thematically. Triangulation ensured validity and credibility. Findings: Statistical results showed no significant difference between expectations and perceptions (t = 0.40, p = 0.69), with a negligible mean gap (0.02). However, qualitative data revealed that the apparent alignment stemmed from structurally low expectations, limited educational relevance, trauma, and underinvestment. Women perceived minimal services as “good enough,” reflecting constrained standards rather than actual satisfaction. Novelty: This is among the first studies in Cambodia to apply the Servqual model to women’s prison education using both quantitative and gender-sensitive qualitative data. It highlights the systemic neglect of incarcerated women’s educational rights and argues for trauma-informed, gender-responsive reforms to ensure prison education is truly rehabilitative.